The Effect of Four Pillars Education on Diabetes Mellitus Disease on Self Efficacy at Rsud Rejang Lebong in 2023 - Kurniawan, Erik; Murwati, Murwati; Azissah, Danur (Student Scientific Journal, 2024)
Based on data from the World Health Organization (WHO) in 2016, 70% of the total deaths in the world and more than half of the disease burden. 90-95% of Diabetes cases are Type 2 Diabetes which is largely preventable because it is caused by an unhealthy lifestyle (World Health Organization (WHO) Global Report, 2016). The research method carried out with a quasi-experimental research design (Quasi Experiment) with The One Group Pre-Post Test approach (The One Group Design), which is a research method carried out with the main objective of making a description or descriptive of a situation objectively (Notoatmodjo, 2010). The population in this study were patients with diabetes mellitus at Rejang Lebong Hospital in 2022, totaling 54 people, the number of samples in this study were 35 respondents. The results of this study showed that some respondents 19 (54.3%) before being given self efficacy education were not good at Rejang Lebong Hospital in 2023, most of the respondents 23 (65.7%) after being given good self efficacy education, there was an effect of four pillars education on diabetes mellitus disease on self efficacy at Rejang Lebong Hospital in 2023 (p value 0.017). The results of this study suggest that the RSUD can provide services by providing education, especially for patients with diabetes mellitus so as to increase self-efficacy.